Inter-comparison of lidar and ceilometer retrievals for aerosol and planetary boundary layer profiling over Athens, Greece - Tsaknakis, Georgios; Papayannis, Alexandros D.; Mamouri, Rodanthi-Elisavet; Kokkalis, Panagiotis; Amiridis, Vassilis; Kambezidis, Harry D.; Georgoussis, Georgios; Avdikos, Georgios K. (My University, 2011)
This study presents an inter-comparison of two active remote sensors (lidar and ceilometer) to determine the mixing layer height and structure of the Planetary Boundary Layer (PBL) and to retrieve tropospheric aerosol vertical profiles over Athens, Greece. This inter-comparison was performed under various strongly different aerosol loads/types (urban air pollution, biomass burning and Saharan dust event), implementing two different lidar systems (one portable Raymetrics S.A. lidar system running at 355 nm and one multi-wavelength Raman lidar system running at 355 nm, 532 nm and 1064 nm) and one CL31 Vaisala S.A. ceilometer (running at 910 nm). Spectral conversions of the ceilometer's data were performed using the Ångström exponent estimated by ultraviolet multi-filter radiometer (UV-MFR) measurements. The inter-comparison was based on two parameters: the mixing layer height determined by the presence of the suspended aerosols and the attenuated backscatter coefficient. Additionally, radiosonde data were used to derive the PBL height. In general, a good agreement was found between the ceilometer and the lidar techniques in both inter-compared parameters in the height range from 500 m to 5000 m, while the limitations of each instrument are also examined.
Keywords: Cloud Height Indicator; Troposphere; Convective Boundary Layer